(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
Financial literacy of the population, including such a social group as students, determines the level of development of the state economy. Ignorance of the basics of financial literacy can lead to serious risks not only for individual credit, insurance companies and their clients, but also for society as a whole. For this reason, a number of countries are implementing programs to improve the financial literacy of the population. Knowledge of financial fundamentals leads to a reduction in cases of overdue loans, reducing the number of cases of financial fraud and eliminates the population from buying unprofitable financial products.